Data for the study entitled: "The effect of PCL addition on 3D-printable PLA/HA composite filaments for the treatment of bone defects" - Åkerlund, Elin; Grzeszczak, Ana (Uppsala University, 2022)
This dataset contains the result files of the experiments conducted within the study for which the manuscript was entitled "The effect of PCL addition on 3D-printable PLA/HA composite filaments for the treatment of bone defects".

This dataset contains the result files of the experiments conducted on PCL/PLA/HA filaments. It includes: result files from XRD, DSC, TGA, FTIR, and SEM analysis. It also includes the Excel documents created to study the data. It also includes files created in Origin for visualization.

OPJ formats are usually opened with the software Origin. For users that do not have access to the software, a free version called “Origin viewer” is available online. With the viewer, the user can open and view the files. The XY formats can be opened in Excel with text import, or Legacy text import.

The dataset was originally published in DiVA and moved to SND in 2024.

Datasetet innehåller resultatfilerna för de experiment som utfördes inom ramen för den studie vars manuskript hade titeln "The effect of PCL addition on 3D-printable PLA/HA composite filaments for the treatment of bone defects".

Se engelsk beskrivning för mer information.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data for the study entitled: "The effect of PCL addition on 3D-printable PLA/HA composite filaments for the treatment of bone defects"
Keywords: Hydroxyapatites; Hydroxiapatiter; polylactic acid; polymjölksyra; Engineering Science with specialization in Materials Science; Teknisk fysik med inriktning mot materialvetenskap; Engineering Science with specialization in Biomedical Engineering; Teknisk fysik med inriktning mot medicinsk teknik; Materials Engineering; Materialteknik